Co-occurrence of Species in Catches from Multi-day Trawlers along North-east Arabian Sea – Implications for Resource Predictions - Kumar, Nimit; Madhu, V R; Meenakumari, B (Fishery Technology, 2025)
Conventional approaches for prediction of fishery resource abundance use remote sensing data of chlorophyll concentration along with secondary parameters such as sea surface temperature, wind speed and direction. The knowledge of co-occurrence of species can help as an input for developing ecological models for species specific predictions. This study attempts to understand abundance and co-occurrence of species in fish catches from commercial multiday bottom-trawling operations carried out over the shelf off Gujarat, based on data collected during 2004-2008. We found that ribbonfish dominated the fishery in this region and was accompanied by lizard-fishes, cuttlefishes and perches; indicating a co-occurrence of species based on the prey preferences.